Secular trend of anthropometric parameters of newborns in municipalities of Tuzla Canton (1976 – 2007) - Amela Begić; Jasminka H. Halilović; Lejla Mešalić; Sabina H.Halilović (Medicinski glasnik, 2016)
Aim: To determine the acceleration of birth weight and birth length of newborns in the municipalities of Tuzla Canton in the last four decades. Tuzla Canton (TC) as an administrative territorial unit of the FBiH includes 13 municipalities. Methods: In this retrospective study data from the Protocol Book of Gynecology and Obstetrics Clinic, University Clinical Center, from 1976 to 2007 were used. The sample of live-born infants by municipalities was divided into four sub-samples: a subsample of infants born in 1976, 1987, 1997 and 2007. During the monitored years there were 19,312 live births in Tuzla Canton (TC), but the study included 17,907 newborns of both sexes. Statistical data processing was performed using standard methods, descriptive and inference statistics. Results: Ascertained results of the secular trend for birth weight showed that this parameter had positive values in seven municipalities, but in six municipalities it was negative. The highest values of increasing birth length of newborns, which were statistically significant, were found in the municipalities of Srebrenik and this increase was 0.06 cm per year. Conclusion: Different values of the secular trend in the monitored TC are result of different socio-economic and ecological conditions in these municipalities, as well as of violent mass population migration that occurred as a result of the war in BiH in the period from 1992 to 1995.
Keywords: acceleration; birth length; birth weight